Nutrient regulation of ß-cell function: what do islet cell/animal studies tell us? - Carlessi, Rodrigo; Keane, Kevin; Mamotte, C.; Newsholme, Philip (Nature Publishing Group, 2017)
Diabetes mellitus is widely recognised as one of the most serious metabolic diseases worldwide, and its incidence in Asian countries is growing at an alarming rate. Type 2 diabetes (T2DM) is closely associated with age, sedentary lifestyle and poor diet. In T2DM, ß-cell dysfunction will occur before hyperglycaemia develops. Excessive levels of glucose, lipid and various inflammatory factors interact at the level of the pancreatic islet to promote ß-cell dysfunction. Pancreatic ß-cell lines have been widely utilised since the early 1980s and have contributed a large volume of important information regarding molecular, metabolic and genetic mechanisms that regulate insulin secretion. The purpose of this review is to describe the origin and characteristics of the most commonly used ß-cell lines and their contribution to discovery of fundamental regulatory processes that control insulin production and release. Pancreatic islets obtained from rodents as well as other animals have additionally provided information on the architecture and three-dimensional design of this endocrine tissue that allows precise regulation of hormone release. Understanding the nature of failure of physiologic and metabolic processes leading to insufficient insulin release and subsequent diabetes has allowed development of novel anti-diabetic therapeutics, now in common use, worldwide.European Journal of Clinical Nutrition advance online publication, 19 April 2017; doi:10.1038/ejcn.2017.49.